Strand 1: Supporting a Culture of Collaborative Study: Collaborative Study in Undergraduate Courses using a Computer-Based Conferencing System - Rimmershaw, Rachel (Proceedings of the International Conference on Networked Learning, 1998)
In this paper I present an account of four short undergraduate courses which ran between 1992 and 1995, three using a computer-based conferencing system (FirstClass) to support collaborative study practices, and one using a paper-based conference for the same purpose. The seriousness of the emphasis on collaborative study was communicated to the students not only by means of the conference discussions, but through the use of student writing as set reading material for the course, and the use of material from the conference discussions as the basis for the final examination. Students responded best in courses in which the tutor participated in conference discussions in a similar style to them. Even when some of the computer-based features were lost, as in the final course which used a paper file for public writing, students made significant use of this forum. However factors outside the design of the system for supporting collaboration seemed to play the strongest part in determining the extent to which students would find value in using the system. Among the factors influencing the success of the course 'philosophy' appeared to be the physical conditions, the initial induction process, the tutor's participation style, and the assessment practices. None of these are particularly surprising, but the experiences reported here indicate that learners respond differently co quite fine differences in the instantiations of the course design.